Financial and Temporal Advantages of Virtual Consultation in Veterans Requiring Specialty Care. Issue 1 (11th December 2017) - Abbott, Daniel E; Macke, Ryan A; Kurtz, Jodi; Safdar, Nasia; Greenberg, Caprice C; Weber, Sharon M; Voils, Corrine I; Fisher, Deborah A; Maloney, James D
Abstract: Background: Access to specialty health care in the Veterans Affairs (VA) system continues to be problematic. Given the potential temporal and fiscal benefits of telehealth, the Madison VA developed a virtual consultation (VC) mechanism to expedite diagnostic and therapeutic interventions for Veterans with incidentally discovered pulmonary nodules. Materials and Methods: VC, a remote encounter between referring provider and thoracic surgeon for incidentally discovered pulmonary nodules, was implemented at the Madison VA between 2009 and 2011. Time from request to completion of consultation, hospital cost, and travel costs were determined for 157 veterans. These endpoints were then compared with in-person consultations over a concurrent 6-mo period. Results: For the entire study cohort, the mean time to completion of VC was 3.2 d (SD ± 4.4 d). For the 6-mo period of first VC availability, the mean time to VC completion versus in-person consultation was 2.8 d (SD ± 2.8 d) and 20.5 d (SD ± 15.6 d), respectively ( p < 0.05). Following initial VC, 84 (53%) veterans were scheduled for virtual follow-up alone; no veteran required an additional office visit before further diagnostic or therapeutic intervention. VA hospital cost was $228 per in-person consultation versus $120 per episode for VC – a 47.4% decrease. The average distance form veteran home to center was 86 miles, with an average travel reimbursement of $112 per in-person consultation, versus no travel cost associated with VC. Conclusions: VC for incidentally discovered pulmonary nodules significantly decreases time to consultation completion, hospital cost, and veteran travel cost. These data suggest that a significant opportunity exists for expansion of telehealth into additional practice settings within the VA system.